The Income Contribution of Women Mobile Vegetable Traders to the Family Economy During the Covid-19 Pandemic in Masagena Village Konda District South Konawe Regency - Ainun Jariyah; Ilma Sarimustaqiyma Rianse; Fahria Nadiryati Sadimantara (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
This research is motivated by the income generated by the husband is deemed insufficient to meet household needs. Hence, women from poor households work to earn sufficient income for the household economy. Mobile vegetable traders on the family economy during the covid-19 pandemic in Masagena Village, Konda District, South Konawe Regency. The research area's determination was performed purposively considering that Masagena village is an area for mobile vegetable traders. The number of respondents was 26 female itinerant vegetable traders. Data analysis used income analysis, and the income contribution was a percentage. The average monthly income of female vegetable traders is IDR13,285,000, with a total monthly cost of IDR10.845.537 and monthly revenue of IDR2.436.463. In contrast, the husband's income from female vegetable traders is IDR1,933,269, with a total monthly cost of IDR564.473 and a monthly income of IDR1.375.694. The income contribution of women travelling vegetable traders during the covid 19 pandemic is 63.91%. The husband's contribution is 36.09%.